Description of early ontogeny and osteological development of streaked mojarra Eugerres lineatus (Teleostei: Percoidei: Gerreidae) - Ortíz-Galindo, José Luis; Castro-Aguirre, José Luis; Balart, Eduardo F.; Álvarez-Pliego, Nicolás (Zootaxa, 2008)
Embryos, larvae, and juveniles of the streaked mojarra Eugerres lineatus are described and illustrated from a series of laboratory specimens. The description was based on morphometry, pigmentation pattern, squamation sequence, and osteological development. The eggs were obtained by stripping ripe adults captured in Bahía de La Paz, Baja California Sur, México. Eggs (cleavage egg and embryo phases) had a mean diameter of 0.69 mm with an oil globule of 0.19 mm mean diameter. Eleutheroembryos were 1.05 mm mean notochordal length (NL) at hatching. The yolk sac was absorbed by 2.10 mm mean NL, underwent notochord flexion at 3.16 mm NL-3.86 mm standard length (SL), and transformed to juveniles at 10.0 mm SL. Juveniles were completely scaled by 14.0 mm SL. Osteological development of the neurocranium, jaws and suspensorium, opercular series, hyoid and branchial arches, vertebral column and ribs, and the paired and unpaired fins and the supports were studied. The identification of the earliest stages of development of E. lineatus compared to the other gerreids and allied taxonomic groups present along the northwestern Mexican coast is possible only in the juvenile period (24.1 mm SL), based on anal fin ray count (II, 9-III, 8), the presence of papilliform teeth, and the number of gillrakers on the lower first pharyngeal arch (15–20).